The Cambridge companion to Black theology - Hopkins, Dwight N.; Antonio, Edward P. (Cambridge ; New York : Cambridge University Press, 2012)
"This volume discusses normative theological categories from a black perspective and argues that there is no major Christian doctrine on which black theology has not commented. Part One explores introductory questions such as: what have been the historical and social factors fostering a black theology, and what are some of the internal factors key to its growth? Part Two examines major doctrines which have been important for black theology in terms of clarifying key intellectual foci common to the study of religion. The final part discusses black theology as a world-wide development constituted by interdisciplinary approaches. The volume has an important role in bringing Christian thought into confrontation with one of the central challenges of modernity, namely the problem of race and racism. This Companion puts theological themes in conversation with issues of ethnicity, gender, social analysis, politics and class and is ideal for undergraduate and graduate students"--
Historical perspective / Gayraud S. Wilmore -- Black theology and liberation theologies / Edward P. Antonio -- The social sciences and rituals of resilience in African and African American communities / Linda E. Thomas -- Black theology and womanist theology / Delores S. Williams -- God / Dennis W. Wiley -- Jesus in Black theology : the ancient ancestor visits / Julian Kunnie -- Black theology and the Holy Spirit / Garth Baker-Fletcher -- Black theology and human purpose / Riggins R. Earl, Jr. -- Theology's great sin : silence in the face of white supremacy / James H. Cone -- Theodicy : 'de Lawd knowed how it was' : Black theology and Black suffering / Allan Boesak -- Black theology and the Bible / Michael Joseph Brown -- Protestant ecclesiology / Jeremiah A. Wright, Jr. -- Roman Catholic ecclesiology / Cyprian Davis -- Dignity and destiny : Black reflections on eschatology / J. Deotis Roberts -- The history of Black theology in South Africa / Mokgethi Motlhabi -- Black theology in Britain / Anthony Reddie -- Slave religion and Black theology in Brazil / Walter Passos -- Black theology in Cuba / t
Includes bibliographical references and index.
Keywords: Black theology